KAJIAN POTENSI PEMBENTUKAN AIR ASAM TAMBANG DARI TANAH LAPISAN PENUTUP BATUBARA ASAL KABUPATEN TELUK BINTUNI - Markus Heryanto Langsa (Jurnal Natural, 2018)
Acid mine drainage is formed when certain sulfide minerals in rocks are exposed to oxidizing. Upon exposure to oxidizing conditions, these sulfide minerals are oxidized in the presence of water and oxygen to form highly acidic, sulfate-rich drainage. Acidity levels, and metal composition and concentration depend on the type and amount of sulfide mineral and the presence or absence of alkaline materials. If acid mine drainage has formed, it will be very difficult to stop the process as it is a continuous process until one of the reactions runs out. Acidic water containing heavy metals when flowing into rivers, loker or swamps will damage the condition of the ecosystem in the river. This will certainly cause a decrease in water quality. The purpose of this study is to examine the potential for the formation of acid mine drainage based on the acid base balance method. The results obtained in samples A, B1, B2, and C for the pasta pH test were 5.25, 4.20, 4.71, and 3.14, respectively. The results of the other parameters for the four samples were total sulfur contents (0.005%, 0.021%, 0.008%, 0.47%), acid neutralization ability (3.1, 2.82, 2.45, 13.07 kg H2SO4/ton), maximum acidic potential (0.153, 0.643, 0.245, 14.394 kg H2SO4/ton) and acid-base balance expressed as potential acid production (-12.917, -2.177, -3.065, 11,944). Evaluation of sample C data based on acid-base balance values (11.944 kg H2SO4/ton) and KPA/PKM ratio (<2, 0.17) indicating that sample C has the potential to form acid mine drainage if the coal mining process is carried out.